Upaya Pencegahan Korupsi Pengadaan Barang dan Jasa Pemerintah Melalui Instrumen Harga Perkiraan Sendiri - Jamila Lestyowati (Faculty of Law, Andalas University, 2019)
This study aims to analyze cases of corruption that occur in the procurement of government goods and services through the owner estimate (HPS) instrument. Corruption in the procurement of goods and services is ranked second after the bribery case. The preparation and determination of HPS as an important part of the procurement of goods/services implementation process carried out by the Committing Officer (PPK). HPS was prepared before the PBJ implementation process. By the provider, HPS is used as a basis for bidding. Meanwhile, by procurement officials and ULP, HPS is the basis for evaluating bids. Analysis using normative methods with qualitative approaches with primary and secondary data. The results showed that corruption cases in the procurement planning are caused by a mistake in the preparation of HPS. The mistake was caused by the HPS compiled by the vendor. PPK lacked the substance of the work and the case of mark up prices. Another cause was the data available for the preparation of HPS is so diverse that PPK compiles HPS without going through expertise calculations. The application of criminal law in the PBJ case is expected to be able to sustain the implementation of good government and public services through the State Budget. That goal can be achieved through the preparation of the right HPS so as to minimize the occurrence of corruption in Indonesia.